EMPOWERMENT OF DISABLED PEOPLE THROUGH SOCIAL AND ECONOMIC INCLUSION PROGRAMS - Fadilah, Shifa; Hafrizal, Irham (Bina Bangsa International Journal of Business and Management, 2025)
Empowering people with disabilities is an important effort in realizing an inclusive and just society. Disabled people often face various barriers to social and economic participation, such as discrimination, stigma, and lack of access to services and opportunities. Therefore, social and economic inclusion programs are very important to improve their quality of life and independence. The social inclusion program aims to eliminate social barriers faced by disabled people, such as stigma and discrimination. This program includes increasing public awareness about the rights and potential of disabled people, as well as providing inclusive services, such as education, health and recreation. The economic inclusion program aims to increase the participation of disabled people in economic activities. This program includes providing skills training, access to business capital, and inclusive job creation. Apart from that, this program also encourages the development of micro, small and medium enterprises (MSMEs) owned by people with disabilities. Implementation of social and economic inclusion programs requires cooperation from various parties, including the government, civil society organizations, the private sector and the general public. The government plays a role in creating policies and programs that support the inclusion of people with disabilities. Civil society organizations play a role in providing services and advocacy for people with disabilities. The private sector plays a role in creating inclusive employment opportunities and supporting MSMEs for people with disabilities. The general public plays a role in creating an inclusive and friendly environment for people with disabilities. Empowering people with disabilities through social and economic inclusion programs has a significant impact. This program can improve the quality of life and independence of people with disabilities, reduce poverty and inequality, and create an inclusive and just society.